Empirical Study on Capital Structure Determinants in Chinese Listed Companies - Zhang, Jiye (2010)
This paper develops a preliminary study to investigate the determinants of capital structure of Chinese-listed companies using panel data. The analysis of the research is based on the dataset of 200 Chinese listed firms which publicly traded A-shares on both Shanghai and Shenzhen Stock Exchange between 2005 and 2009. The different theories, specifically, the trade-off, pecking order, agency theory, market timing and signalling theories, are deployed to clarify and predict the signs and significance of each factor identified by Ragan and Zingales (1995) and Booth et al. (2001). The book value of total liability ratio is employed as the main proxy for the measure of leverage in this research. Eight elements have been selected as explanatory variables which predict to have significant impacts on the capital structure of Chinese listed firms. Non-debt tax shields and inflation are estimated to have a negative relation with the firm’s leverage, but statistical insignificant. However, the Profitability has a significant negative relationship with firm’s leverage. It follows the underlying logic of pecking order theory. Tangibility and volatility are strongly positively linked to the firm’s debt level, which support the predictions of trade-off theory. Size is also strongly positively correlated to the debt level. Growth opportunity has significant positive effect on leverage. Furthermore, the effective tax rate also has positive relation with leverage, but it is insignificant with debt level. The findings show that the agency theory, market timing and signalling theory are not applicable to Chinese listed companies. In addition, the mean of long-term debt is pretty lower, which implies the Chinese firms tend to have much lower long-term debt.